EVALUATION OF OBSTACLES TO TAXPAYER EXTENSIFICATION OF MICRO, SMALL AND MEDIUM ENTERPRISES IN GUBENG DISTRICT, SURABAYA CITY AFTER THE ENFORCEMENT OF GOVERNMENT REGULATION NUMBER 46 OF 2013 - Lintang Nahdya Putri; Made Dudy Satyawan (Universitas Airlangga, 2016)
This study aims to evaluate extensification activities after the enactment of PP No. 46 of 2013 at KPP Pratama, Gubeng City of Surabaya. There are three ways to carry out extensification activities. The methods are to visit the location of MSMEs (Micro, Small, Medium Enterprises), collect data on owners from MSMEs, and provide a letter of application for registration. Data collection techniques using interviews and documentation. Then, the data were analyzed using source and theory triangulation. The results of this study conclude that there are factors that become obstacles to extensification activities at KPP Pratama Gubeng Surabaya City, namely being less active in carrying out extensification activities, SME owners avoidance when extensification activities take place, and MSME owners lack an understanding of taxes.